Archiving. Issue 4 (2nd July 2019) - Patchett, Merle
Abstract : What do animals teach us about historiography? This intervention explores this provocation by restaging a methods workshop that sought to radically rethink the archive as animal and archiving as an iteration of animal play and politics. To do so it recounts what happened when a group of human geography Master's students, armed only with a few key readings and some gloves, were introduced to a collection of feathered remains. With no interpretive materials to accompany these remains, the students were prompted to respond to their immediacy and materiality and thus place them at the heart of archival enquiry.